2015
DOI: 10.1080/13557858.2015.1044946
|View full text |Cite|
|
Sign up to set email alerts
|

Between power and powerlessness: a meta-ethnography of sources of resilience in young refugees

Abstract: The results, from an ecological developmental perspective, stressed the interplay between protective and risk processes in the mental health of young refugees who had resettled in Western countries, and they emphasized the variability as well as the universality of resilience-promoting processes. Further research is needed to explore the cultural shape of resilience and the long-term consequences of war and migration on young refugees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 73 publications
(48 reference statements)
6
136
0
6
Order By: Relevance
“…To date, there are few evidence based family-level interventions for refugees that address the stressors families face after third country resettlement [55]. This is a major shortcoming given the role family functioning among refugees can play in both promoting resilience and contributing to adverse outcomes of youth [56, 57]. And while addressing the mental health impact of exposure to discrete traumatic events experienced by refugees is extremely important, there is also a need to provide services that have a broader focus [58].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few evidence based family-level interventions for refugees that address the stressors families face after third country resettlement [55]. This is a major shortcoming given the role family functioning among refugees can play in both promoting resilience and contributing to adverse outcomes of youth [56, 57]. And while addressing the mental health impact of exposure to discrete traumatic events experienced by refugees is extremely important, there is also a need to provide services that have a broader focus [58].…”
Section: Discussionmentioning
confidence: 99%
“…Sleijpen et al [25] in a review of 26 studies identified the following six sources of resilience, most of which also had counterproductive aspects, in young refugees, who had resettled in Western countries: social support, acculturation strategies, education, religion, avoidance, and hope. Resilience assessed 20 years after displacement of Sri Lankans proved to be more strongly and robustly associated with economic and social factors than with the presence of mental disorders.…”
Section: Mental Health Problems As Reported In Studies Published In 2015mentioning
confidence: 99%
“…A recent meta-ethnography of qualitative research conducted among refugee youth found common sources of strength across studies: social support, acculturation strategies, education, religion, avoidance and hope (Sleijpen, Boeije, Kleber, & Mooren, 2016). Many of the youth screened in SBHC A noted an optimistic outlook and positive views of their own academic strengths, support from teachers and opportunities for sports participation.…”
Section: Supports For Resiliencementioning
confidence: 99%